„Do Tadeusza Estreichera”. Kolor niebieski w procesie twórczym Stanisława Wyspiańskiego - Bajda, Justyna (Przestrzenie Teorii, 2024)
This paper undertakes an analysis of a rhymed letter by Stanisław Wyspiański sent in December 1904 to Tadeusz Estreicher, taking into account the perspective of ‘visual thinking’, proposed by Rudolf Arnheim in his book Visual Thinking, and the category of ‘colour’. The text emphasizes the role of the particular colour particular colour – blue, which had a special significance in the creative process of the painter and poet. Blue accompanied Wyspiański in his letters, dramas, poetry, and eventually also in the interior of his studio on Krowoderska Street. Everywhere (including in his poetic letter to Estreicher), it played a unique role – it allowed him to express the need to surround himself with the most airy colour and to immerse himself in the ‘blue atmosphere of freedom’.